Penerapan Prinsip Good Governance dalam Pengelolaan Proyek Penanggulangan Kemiskinan di Perkotaan - Erfina ina (JIA: Jurnal Ilmiah Administrasi, 2012)
Abstract The goal of this research is to determine: one, the application of good governance principle to manage urban poverty relief project. Two, the obstructive factors in applying good governance principle to manage urban poverty relief project. The methods used to collect data are: (1) observasion, (2) questionaire, (3) interview, (4) literature study. The population and samples takes eighty-one (81) people. And the data analysis technique used is qualitative-descriptive analysis. The conclusions: (1) the application of good governance principle to manage urban poverty relief project has not yet reached maximal target. The target reached only 36,49%. (2) The obstructive factors in applying good governance principle are: (a) less optimal officers' performance that shows 34,57% percentage. The reason is lack of awareness to accomplish the job and responsibility. (b) family-center culture is thick, which shows 48,14% percentage. In context of poverty relief, it lacks objectivity and less-accurate target. (c) less amount of society's participation which shows 48,15% percentage. The reason is also lack of awareness and sense of belonging to the program.